CHARACTERIZATION OF CONTINUOUS E-GLASS AND BASALT FIBER REINFORCED ISOPHTALIC POLYESTER MATRIX COMPOSITES - Gumulcine, Tugcegul; Bekem, Aylin; Dogu, Mustafa; Gemici, Zafer; Unal, Ahmet (YILDIZ TECHNICAL UNIV, 2013)
In present, the demand for composites showing various characteristics and diversifying raw-materials is growing for technological/advanced technological applications. The utilization of E-glass fiber as a reinforcement comes out in general purpose polymer composite applications. Basalt fiber is relatively developed as an alternative material and its properties are still being investigated. In this study, thermosetting isophtalic polyester resin was reinforced with two kinds of continuous E-glass fiber and two kinds of basalt fiber. The properties of produced composite materials were determined by applying physical and mechanical tests and the priorities of fiber types on each other were determined. Consequently, it was observed that basalt fibers exhibited better properties than E-glass fibers. Fiber diameter and density (tex) was also important to obtain this conclusion.
Keywords: Composite; thermoset matrix; E-glass fiber; basalt fiber; isophtalic polyester resins; Engineering